Big Bird, Binders, and Bayonets: Humor and live-tweeting during the 2012 U.S. Presidential Debates - Driscoll, Kevin; Ananny, Mike; Bar, François; Guth, Kristen; Kazemzadeh, Abe; Leavitt, Alex; Thorson, Kjerstin (AoIR Selected Papers of Internet Research, 2013)
During the 2012 U.S. election cycle, social media analytics services were eager to demonstrate the efficacy of their tools to capture public opinion on Twitter. Graphics they produced to illustrate user sentiment regarding the candidates and issues were later reproduced by major news organizations. To better understand the particular practices that undergird such summary representations, we collected 35,247,043 tweets during the three televised presidential debates, nearly half of which were made up of retweets. Using a combination of quantitative content analysis and software-assisted close textual analysis, we examined the use of humor and sarcasm, ’astroturfing’ by campaigns and other strategic actors, and the prevalence of retweeting ’bots.’ Although sentiment analysis systems rarely disclose their methodologies, the diverse practices we encountered in this corpus makes clear that large-scale computational methods must account for the local contexts within which tweets are produced if they are to report meaningful statistics.